2016
DOI: 10.1136/bjsports-2015-095748
|View full text |Cite
|
Sign up to set email alerts
|

Injury and illness surveillance at the International Sailing Federation Sailing World Championships 2014

Abstract: The Olympic classes introduced since 2000 (49erFX, 49er, Nacra 17) have resulted in a rise in injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…10 Epidemiologic studies of sports injury and illness have since been conducted using injury-surveillance systems, not only during multi-sports events such as the OGs and Youth OGs, 5,6,1013 but also single-sport events. 1419…”
Section: Introductionmentioning
confidence: 99%
“…10 Epidemiologic studies of sports injury and illness have since been conducted using injury-surveillance systems, not only during multi-sports events such as the OGs and Youth OGs, 5,6,1013 but also single-sport events. 1419…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that high wind speeds increase the risk of injury among sailors. 8,[10][11][12][13] Only 1 published study, by Rouvillain et al, 14 attempted to describe the injuries associated with sailing in the cruising population. Their results suggest that most of the injuries reported could have been prevented if a few simple recommendations had been implemented (wearing shoes, using a hatch cover, a bimini top, a windlass, and adequate wound care).…”
Section: Introductionmentioning
confidence: 99%
“…7 Only 1 study has examined the spectrum of medical issues encountered during a transatlantic race. 1 In contrast, extensive research highlights the common injuries experienced in sailing, 8,9 river rowing, 10,11 and kayaking/canoeing. 12…”
Section: Introductionmentioning
confidence: 99%